Digital Transformation in Public Administration: Innovations, Challenges and Opportunities - Ninyuk, Inna I. (Futurity Research Publishing, 2024)
This study aims to examine the nature of change processes in public administration, the nature of innovation in this area, and the challenges associated with changes in the field of digitalization. Using the experience of several countries, the study outlines the leading digital solutions, such as e-government and artificial intelligence, as well as the main challenges, such as cyber threats and organizational barriers. The results show that the successful case studies used by different governments to overcome the difficulties emphasize the value of synergies and adaptive management. These results are essential for policymakers if they are interested in improving digital governance in the public sector.
Keywords: цифрова трансформація; digital transformation; public administration; e-government; challenges; innovations